The Marriage Metaphor in Nineteenth-Century English Canadian Fiction - Murphy, Carl (Studies in Canadian Literature, 1988)
In Julia Beckwith Hart's St. Ursula's Convent, William Kirby's The Golden Dog, and Frances Brooke's Emily Montague, the recurring theme of marriage between French and English characters is in each case a metaphor for the desired unity between the "two solitudes," in which confederation is prefigured. In most of the novels discussed, the glorious (if nostalgic) French and British histories and traditions are united optimistically with a largely hopeful future. This unification of two nations in one land is the distinguishing factor between the whole of nineteenth-century Canadian fiction and its European counterparts.